The Electrochemical Characterization of Functionalized Isoindolinones - Daniel. E. Smith; Ashley J. Basson; Niamh J. Owen; Mark Potter; Mark G. McLaughlin; Kathryn E. Toghill (ChemElectroChem)
This study considers the electrochemical and physical properties of six functionalized isoindolinones, synthesized using a facile, green route. The compounds show redox activity at a highly negative potential with quasireversible redox potentials of ≈−2.8 V versus Fc/Fc+, a potential in the region of alkali metal deposition and intercalation. For those molecules with a specific structural motif, the electrochemical behavior is electrochemically quasireversible, attributed to the formation of a carbanion radical stabilized on the carbonyl group. The electrochemical properties of the reversible compounds are assessed, with the lead‐performing compound extensively characterized galvanostatically to assess its candidacy for nonaqueous, high‐voltage energy storage.